2008
DOI: 10.1007/s10803-008-0608-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Eye-Movement Patterns During an Embedded Figures Test in Children with ASD

Abstract: The present study examined fixation frequency and duration during an EFT in an effort to better understand the attentional and perceptual processes by which individuals with ASD achieve accelerated EFT performance. In particular, we aimed to elucidate differences in the patterns of eyemovement in ASD and TD children, thus providing evidence relevant to the competing weak central coherence and enhanced perceptual functioning theories. Consistent with prior EFT studies, we found accelerated RT in children with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
3
31
2
Order By: Relevance
“…triangle or house shape) within a larger complex abstract design. The time taken to correctly spot the simple shape in the 12 complex pictures is recorded, and has been shown to distinguish individuals with autism from controls (De Jonge et al 2006;Keehn et al 2008). Following the modified procedure of Shah and Frith (1983) and Ropar and Mitchell (2001), the children were allowed to indicate the hidden figure by using their finger or a stylus pen without ink to trace the simple shape.…”
Section: Dependent Measuresmentioning
confidence: 99%
“…triangle or house shape) within a larger complex abstract design. The time taken to correctly spot the simple shape in the 12 complex pictures is recorded, and has been shown to distinguish individuals with autism from controls (De Jonge et al 2006;Keehn et al 2008). Following the modified procedure of Shah and Frith (1983) and Ropar and Mitchell (2001), the children were allowed to indicate the hidden figure by using their finger or a stylus pen without ink to trace the simple shape.…”
Section: Dependent Measuresmentioning
confidence: 99%
“…Poor performance in this motion domain suggests a difference in the processing of simple motion stimuli. In addition ASD individuals outperform typical observers in static tasks such as visual search [15][16][17] and embedded figures tasks [14,18,19] which support a difficulty with grasping the gestalt and being drawn into the finer detail of objects. Thus, according to WCC theory, there is a natural cognitive bias towards the local over the global perspective and superior performance in tasks requiring the detection of detail.…”
Section: Introductionmentioning
confidence: 97%
“…The TD group exhibited faster reaction times (RT) to targets occurring as novel search elements, the ASD group performed similarly in target new and old conditions, indicating impaired attentional prioritization of novel onsets. However, Keehn and Associates [13] Raymaekers, Van Der Meere, and Roeyers [1] found that adults with high functioning autism (HFA) exhibit problems with response inhibition when go/nogo stimuli were presented rapidly, but not when stimuli were presented slow. It was found that performance in adults with HFA was the same as in the control group in the condition with a slow and medium presentation rate, but that it decreased in the condition with a fast presentation rate: many errors of commission were made in this condition.…”
Section: Introductionmentioning
confidence: 99%